An experimental investigation of the effect of a justice violation on pain experience and expression among individuals with high and low just world beliefs. (5th August 2013) - Trost, Z.; Scott, W.; Lange, J.M.; Manganelli, L.; Bernier, E.; Sullivan, M.J.
Abstract Background Perceptions of injustice are linked with poorer physical and psychological outcomes in the context of pain and injury. Violations of injustice can arise out of violations of just world belief (JWB). However, no study has yet examined whether JWB moderates the effect of justice violation on pain experience. Methods The current study examined the effect of an experimental justice violation on acute pain outcomes and whether JWB moderated this effect. Participants completed the JWB scale and then engaged in two cold pressor tasks (CPT). Half the participants were told that the second CPT immersion was part of standard protocol; the other half were told that the painful procedure had to be repeated due to experimenter negligence. Participants provided report of pain intensity following each CPT immersion. Video records of participants undergoing the CPT were coded for presence and duration of pain behaviour. Results Exposure to the justice violation resulted in elevated pain intensity from the first to the second immersion only among participants with high JWB. For participants with low JWB and participants in the control condition, there was no significant difference in pain intensity across immersions. Control participants showed a decrease in pain behaviour from the first to the second immersion. In the negligence/ justice violation condition, reductions in pain behaviour were observed only among participants with low JWB. Conclusions Our results indicate that individuals with high JWB may show particularly adverse reactions in response to justice violations in the context of acute pain experience.